MATHEMATICAL PROGRAMS WITH PRIMARY TURBO PASCAL VERSION 6.0 - Mohammad Latief; Susi Wagiyati P, SKom, MMSI (Jurnal Sistem Informasi, 2002)
To search for prime numbers the most important is the first mining-master the correct multiplication, division and other calculations, after which it understands itself a prime number is a number that can only be number one and number divided by itself, if any number other than number one and number itself , These numbers are not prime numbers.